NUTRITIONAL PROFILE, ANTIOXIDANT, ANTIMICROBIAL POTENTIAL, AND BIOACTIVES PROFILE OF CHLORELLA EMERSONII KJ725233 - Sawant, Sneha Sunil; Kelkar Mane, Varsha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study revolved around the nutritional evaluation of Chlorella emersonii KJ725233, a novel non-fastidious Chlorella strain that was isolated from the Western regions of Maharashtra, India, for a probable use as a food supplement. Methods: The nutritional composition of C. emersonii KJ725233 was evaluated in terms of total protein, total lipids, and total carbohydrates content along with its mineral composition. Furthermore, the effect of different solvents on the extraction of the bioactives and hence the antioxidant and antimicrobial activity of C. emersonii KJ725233 was also analyzed. The bioactives extracted in the organic solvents were further identified by gas chromatography–high-resolution mass spectrometry (GC-HRMS). Results: As reported in the literature for commercial Chlorella powder, C. emersonii KJ725233 was found to contain an equivalent concentration of protein, three-fold lipid content, i.e. 36.48±0.52% and 43.58±0.72%, respectively; along with 17.17±0.91% carbohydrates and 6.62±0.16% mineral content. Methanolic content was not only found to contain the highest antioxidant, radical scavenging potential as well as total phenolic content but also exhibited a strong antimicrobial potential against the tested Gram-positive, Gram-negative bacterial and fungal strains. Moreover, sterols, hydrocarbons, and fatty acid methyl esters known antimicrobials and antioxidants were identified when the organic extracts of the microalgae dried biomass were subjected to GC-HRMS analysis. Conclusion: With a well-balanced nutritional composition together with the reservoir of antioxidants and antimicrobials, this native novel isolate of Chlorella thus emerges as a potential food supplement whose consumption would not only enhance the dietary value along with providing antiaging benefits.